1994
DOI: 10.1203/00006450-199401000-00006
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inhaled Nitric Oxide on the Pulmonary Circulation of the Neonatal Pig

Abstract: ABSTRACT. To study the pulmonary vasodilator selectivity of low levels of inhaled nitric oxide (NO) in a model of neonatal pulmonary hypertension, we sequentially exposed anesthetized, spontaneously breathing neonatal pigs to each of four different inspired gas mixtures: room air, room air with 25 parts per million NO, hypoxia (14% 0 2 in N2), and hypoxia with 25 parts per million NO. The room air, room air with NO, hypoxia, and hypoxia with NO exposures were of 15-min duration. The following measurements were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 8 publications
1
18
1
Order By: Relevance
“…CO changes were not different between groups after DPTA/NO administration, and these findings are similar to those reported previously in NONOate-treated animals with pulmonary hypertension (10,18,20,21,27). Because there was a significant decrease in Ppa and PVR, a significant improvement in CO should be expected.…”
Section: Discussionsupporting
confidence: 78%
“…CO changes were not different between groups after DPTA/NO administration, and these findings are similar to those reported previously in NONOate-treated animals with pulmonary hypertension (10,18,20,21,27). Because there was a significant decrease in Ppa and PVR, a significant improvement in CO should be expected.…”
Section: Discussionsupporting
confidence: 78%
“…Although the values of PAP and PVR in the Clawn miniature pigs were higher than those of the upper limit of the normal canine range (PAP < 20 mmHg, PVR < 250 dyne · s · cm -5 ), the RAP was within the normal canine range (< 6 mmHg), and no compensatory hypertrophy of the right ventricle was recognized in postmortem examination. Fugelseth, Nelin and Rock have reported that the PAP rises in hypoxic pig models [4,10,12]. However, the miniature pigs of our present study were not in a hypoxic state.…”
contrasting
confidence: 53%
“…Since NO is one of the major vasodilators released from vascular endothelial cells to maintain basal dilator tone and to oppose pressor substances in pulmonary vasculature (Moncada et al 1991;Pohl et al 1993), it could also contribute to the reduction of PVR during exercise. Low doses of inhaled NO have been shown to reverse an increased PAP and improve f7-/Q in the neonatal pig (Nelin, Moshin, Thomas, Sasidharan & Dawson, 1994) and during severe pulmonary diseases of man (Bigatello et al 1994;. Inhaled NO (80 p.p.m.)…”
mentioning
confidence: 99%